Problematika Pembelajaran Membaca Al-Qur’an di Madrasah Tsanawiyah Negeri Ujung Gurap Padangsidimpuan - Fitriani, Fitriani (Darul Ilmi: Jurnal Ilmu Kependidikan dan Keislaman, 2020)
This research was conducted using descriptive qualitative methods with a sample of 4 BQ teachers from 8 existing BQ teachers and 33 students (grade VII). Then this research was carried out by collecting interview and observation data while the technique guarantees the validity of the data in this study was to use triangulation. The results of this study have found a change in the attitudes and nature of the students in learning to read the Qur'an at MTs N Ujung Gurap even though the results achieved have not been maximized. This is in accordance with the answers to the interviews with BQ teachers and VII grade students of MTs N Ujung Gurap, namely the implementation of learning to read the Qur'an including planning, implementation, and evaluation. While the obstacles encountered include the lack of student fees, the facilities are still minimal and the allocation of time is lacking, the solution is to provide motivation, utilize existing facilities and make available time efficient